Infrared sensor-based remote controlled driving system for people with lower body disability and leg impairment - Muhammad Arsalan; Faraz Akbar (Mechanical Engineering for Society and Industry, 2023)
The ever-increasing demand for independent mobility has escalated vehicle production across the globe. However, very less focus is given to drivers who are physically impaired or have a driving disability. Thus, the primary purpose of this research is to design a low-cost infrared sensor-based remote-operated driving system for people with lower body disabilities and leg impairment. The presented design is based on an Arduino UNO microcontroller that is programmed and coupled to an infrared sensor to press and release the brake and acceleration pedals, which can be hand-controlled by the disabled driver. Two TB6600 microstepping drivers and NEMA-23 stepper motors have been externally powered using a Volta 12V lead-acid maintenance-free battery at 2.5 amperes with a peak current of 2.7A, and 200 steps/rev. for maximum output torque. An LED and alarm have been placed on the dashboard for an emergency alert or system failure. Additionally, brake and acceleration pedals have been tied to a monofilament cord, which further connects the motor shafts to assist pedalling operation and allows the driver to control the brake and acceleration pedals through an IR remote. The findings comprise two models: theoretical and actual. Results show that theoretical braking time is around 0.7s while actual braking time is found as 0.6s, which shows a good agreement.